Fishermen’s perceptions of constraints on adaptive capacity in the California market squid and California spiny lobster fisheries - Powell, Farrah; Levine, Arielle; Ordonez-Gauger, Lucia (Frontiers in Marine Science, 2022)
Planning for resiliency in the face of unprecedented environmental change requires understanding the factors that constrain fishermen’s capacity to adapt. Scholars have highlighted numerous factors that may facilitate or constrain fishermen’s adaptive capacity, but ultimately fishermen act based on their own perceptions of their ability to respond and adapt to change within their broader social, environmental, and governance context. Subjective assessments of adaptive capacity are limited, yet critical, given that in the face of stressors, people’s actions are facilitated or constrained by their subjective perceptions of their capacity to take action. Using fishermen interviews and feedback sessions, we explored fishermen’s perceptions of constraints on their ability to adapt to change in two fisheries in the California Current System: California spiny lobster and California market squid. Our comparative assessment revealed important similarities and differences with regard to the likelihood that fishermen would perceive a given factor as a constraint, as well as the extent to which different domains of adaptive capacity, including diversity and flexibility in livelihood options, knowledge, and access to physical and financial capital, influence fishermen’s perceptions of constraints. Constraints relating to fishery governance, including permit access, fishery regulations, and broader concerns with fishery management were the most commonly perceived constraints in both fisheries. Individual-level constraints including mobility and knowledge of other fisheries and fishing locations were less frequently cited and significantly more likely to be perceived as constraints by spiny lobster fishermen than market squid fishermen. Our results highlight the importance of considering interactions between factors constraining different elements of adaptive capacity given that the broader governance context of fisheries can inhibit individual-level adaptive strategies. Overcoming barriers to adaptation necessitates planned and participatory governance processes that strengthen fishermen’s individual agency and ability to take meaningful action in the face of change.